An assessment of Amanda Bartolome's Awakening in Lualhati Bautista's Dekada '70 - Calapatan, Jenelyn (Animo Repository, 2005)
This thesis is a study on Lualhati Bautista's award-winning novel Dekada '70. The main objective of the study is to analyze the novel in a feminist perspective by focusing on its main character, Amanda Bartolome. The study identifies the various means of oppression a woman experiences in a patriarchal society. It also reveals how patriarchal ideologies as well as the social construction of gender work in the perpetuation of women's subjugation. Furthermore, the study highlights and at the same time evaluates Amanda's journey to her awakening as a marginalized woman in the society by performing domestic roles as a wife to her husband and a mother to her five sons. The study also indicates the several factors which helped Amanda to realize her oppression including the socio-political environment that is prevalent during her time. At the end of the study, a conclusion is made based on the assessment of Amanda's awakening. Although it was very evident that Amanda was able to experience a gradual awakening from her marginal position, it cannot be considered as truly absolute to liberate herself fully from further means of oppression.